Use of Smart Phone Applications for Clinical Decision Making Among Junior Medical Practitioners in Selected Health Facilities in The Greater Accra Region, Ghana - Senya, K.Y. (University of Ghana, 2015)
The health system in Ghana is fraught with many well documented challenges. Health service delivery is inefficient and unreliable in many respects, access to adequate and reliable health care personnel and services is limited and quality of service delivered at various health facilities continues to be problematic. Among factors hindering quality of service given to clients at health facilities are gaps in clinical decision making and information given to clients. There is evidence that smart phone technology for health is affordable and very applicable in low and middle income countries to help resolve the bottlenecks that hinder improved service delivery in the health sector. This work explores the prevalence of the use of smart phone applications (apps) for clinical decision making among junior medical practitioners in selected health facilities in the Greater Accra Region of Ghana. A total of sixty five junior medical practitioners were randomly selected and surveyed using a structured questionnaire which asked about ownership of smart phones and smart phone apps, frequency of use of apps, commonly used apps and factors influencing usage of apps. The results show a universal ownership of smart phones among junior medical practitioners. Android phones were the most popular type of phone (70.7%) followed by apple i-Phone (16.9%), windows phone (4.6%), other smart phones (6.2%) and Blackberry phones (1.6%). All participants reported they used various smart phone apps for clinical decision making, with web access and drug reference apps being the most popular apps used for clinical decision making. Eighty eight percent (88%) of respondents had third party medical related apps installed on their smart phones. The majority consider their knowledge of information technology as either moderate (52.3%) or high (44.6%), only 3.1% considered themselves to have low knowledge. When available, 64.2% of respondents would prefer to use their smart phone apps for clinical decision making rather than use a hardcopy protocol. The study concludes that there is a very high prevalence of smart phones and smart phone apps ownership. The prevalence of usage of smart phone apps for clinical decision making among junior medical practitioners in the Greater Accra region of Ghana is also very high.
Thesis (MPh) - University of Ghana, 2015